1995
DOI: 10.1159/000236855
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Complaints, Inflammatory Cells and Mediator Concentrations in Nasal Secretions after Nasal Allergen Challenge and during Natural Allergen Exposure

Abstract: A quantitative determination of the inflammatory mediators was performed and correlated with complaints and the measurement of the inflammatory cells in nasal secretions of 18 seasonal allergic rhinitis patients (group 1) outside the pollen season and 40 symptomatic patients (group 2) with seasonal allergic rhinitis during the pollen season. Ten nonallergic subjects (group 3) were also studied as a normal control group. In group 1, 17 (94%) out of 18 patients had an immediate response of nasal symptoms accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
86
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 10 publications
5
86
2
Order By: Relevance
“…It is well known that following activation, mast cells release both vasoactive mediators and chemotactic mediators that attract inflammatory cells such as eosinophils [21, 28, 29, 30]. In the present study, we analysed histamine and tryptase levels in blood and/or nasal fluids from several groups of patients with polyps, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is well known that following activation, mast cells release both vasoactive mediators and chemotactic mediators that attract inflammatory cells such as eosinophils [21, 28, 29, 30]. In the present study, we analysed histamine and tryptase levels in blood and/or nasal fluids from several groups of patients with polyps, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we analysed histamine and tryptase levels in blood and/or nasal fluids from several groups of patients with polyps, i.e. non-allergic patients and patients sensitive either to HDMs or to Parietaria , in order to monitor the mast cell activation, and eosinophil and ECP levels in order to monitor eosinophil involvement [21, 28, 29, 30]. Furthermore, to gain insight into the pathophysiology of nasal polyps, the data were related to the severity of symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, clinical observations have revealed that allergic rhinitis patients show nasal hyperresponsiveness to histamine and LTD 4 (8 -10). Since these chemical mediators have been reported to be involved in the induction of antigen-induced nasal responses (11,12), it is important to evaluate whether antigen-induced nasal responses are intensified when nasal hyperresponsiveness is being developed. However, due to limitations associated with clinical research, an adequate experimental model is indispensable for analysis of this vital issue.…”
Section: Introductionmentioning
confidence: 99%